The tin1 gene retains the function of promoting tillering in maize - Zhang, Xuan; Lin, Zhelong; Wang, Jian; Liu, Hangqin; Zhou, Leina; Zhong, Shuyang; Li, Yan; Zhu, Can; Liu, Jiacheng; Lin, Zhongwei (Nature communications, 2019)
Sweet maize and popcorn retain tillering growth habit during maize diversification. However, the underlying molecular genetic mechanism remains unknown. Here, we show that the retention of maize tillering is controlled by a major quantitative trait locus (QTL), tin1, which encodes a C2H2-zinc-finger transcription factor that acts independently of tb1. In sweet maize, a splice-site variant from G/GT to C/GT leads to intron retention, which enhances tin1 transcript levels and consequently increases tiller number. Comparative genomics analysis and DNA diversity analysis reveal that tin1 is under parallel selection across different cereal species. tin1 is involved in multiple pathways, directly represses two tiller-related genes, gt1 and Laba1/An-2, and interacts with three TOPLESS proteins to regulate the outgrowth of tiller buds. Our results support that maize tin1, derived from a standing variation in wild progenitor teosinte population, determines tillering retention during maize diversification.
Keywords: Plant Development; Plant Proteins; Zea mays; Quantitative Trait Loci; rostlinné geny; vývoj rostlin; Genetic Loci; kukuřice setá; Genes, Plant; Phenotype; Gene Expression Regulation, Plant; rostlinné proteiny; fenotyp; regulace genové exprese u rostlin; lokus kvantitativního znaku; genetické lokusy